Designing a Model of Strategies to Overcome the Limitations of Dealing with Leisure Time with an Emphasis on Physical Activity - Elham Asadzadeh Soure; Farzam Farzan; Mehrdad Moharramzadeh (Research in Sport Management and Marketing)
Purpose: The current research was conducted with the aim of determining the indicators of barriers to leisure time with an emphasis on physical activity and providing a qualitative model of strategies to overcome it.Methods: The research method is qualitative. The community studied in the qualitative part of this research was made up of the staff managers of the Ministry of Sports and Youth of the Islamic Republic of Iran and the heads of sports federations related to public sports. The snowball sampling method continued until theoretical saturation (17 interviews) was reached.The qualitative data analysis process was carried out based on Strauss and Corbin's systematic model in three stages: primary coding, central coding and selective coding. At the end of the three stages of coding, the layers of the final research model were presented individually and schematically, and finally, the final research model was presented by combining these layers.Results: Based on the results, 100 concepts (codes) were extracted from the interviews, which were included in the subset of 21 components and finally formed the sub-branches of the foundation's data model with the Strauss and Corbin approach.Conclusion: The results showed that the model is influenced by various factors. Therefore, when the mechanism of the effect of these factors is correctly identified and diagnosed, we can witness the reduction of restrictions on active sports leisure activities and the increase of participation in active sports leisure activities and the facilitation of negotiations.